Nonlinear electric transport in macromolecular system for stochastic computing. Issue 3 (4th May 2017) - Matsumoto, Takuya; Matsuo, Haruka; Sumida, Saki; Hirano, Yoshiaki; Che, Dock-Chil; Ohyama, Hiroshi
Abstract: Nonlinearity is the vital factor for stochastic computing. Toward the realization of brain-mimetic function using molecular network, the nonlinear electric properties of molecular systems are investigated in nanoscale with atomic force microscopy and nano-gap electrodes. Nonlinear current–voltage characteristics were observed for {Mo154/152 }-ring, cytochrome c, and cytochrome c /DNA networks where the conduction paths includes electron injection into weakly coupled discrete energy levels, electron tunneling through potential well, and electron hopping via Coulomb-blockade network. Stochastic resonance was observed in cytochrome c /DNA network.